Attitudes towards learning English as a Second Language (ESL): the case of students in a rural secondary school in Malaysia - Zulkefly Balan, Farah; Razali, Abu Bakar (International Educational & Social Sciences Association, 2017)
Many research have been done pertaining the issue of students’ attitudes towards learning English as a second language and the factors leading to these attitudes. However, very little is known about how these factors actually affect the students. By applying the sociocultural perspectives based on three theories (i.e., Vygotsky’s (1978) Sociocultural Theory, Spolsky’s (1989) Model of Second Language Learning, and Gardner’s (1985) Second Language Acquisition Theory) this study examines the students’ attitudes towards learning English as a second language in one rural school in the country, involving 6 students from 3 different classes. There were three questions that guided this study, namely: (i) What are the rural secondary school students’ attitudes towards learning the English language?; (ii) What are the sociocultural and psychological factors that contribute to the rural secondary school students’ attitude towards learning the English language?; (iii) How do these sociocultural and psychological factors contribute to the rural secondary school students’ attitude towards learning the English language? Working within the tradition of descriptive and exploratory qualitative research, this study employed a case study approach. A rural secondary school in a southern state in Malaysia was selected with 6 students from 3 different classes as the primary participants. These students were interviewed twice and were observed at least thrice during English lesson in the classrooms. The researchers also analysed their learning materials (i.e. their notes, exercises and homework).